2016
DOI: 10.18203/2319-2003.ijbcp20164755
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different teaching-learning methods according to students’ preference and perception

Abstract: Background: Improved teaching methodology is prerequisite for education systems so that students learn effectively. The present study was done with the objectives of evaluation of different teaching-learning methods according to students’ preference and perception.Methods: It was observational, non-interventional questionnaire based study. Total 100 students were selected randomly from second MBBS as participants of it. They filled questionnaires with 11 questions, by selecting appropriate options.Results: All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…This system therefore requires the best teachers and the teaching methods that can produce the best medical practitioners from the medical students. 14 Effective teaching involves adopting appropriate teaching roles to support learning goals. 15 There is a close association between the student's opinion and the instructor`s effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This system therefore requires the best teachers and the teaching methods that can produce the best medical practitioners from the medical students. 14 Effective teaching involves adopting appropriate teaching roles to support learning goals. 15 There is a close association between the student's opinion and the instructor`s effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…11 Mehta et al also reported the same trend regarding preferred reading material of students in a similar study. 14 This signifies the importance of lectures and an attempt must be made by concerned faculties to enhance the interest and outcome of such classes. The interest in lecture classes can be increased by making classes more interactive, using more diagrams, flow charts, figures and inserting more clinical examples in the classes as these are also the reforms suggested to enhance the interest and outcome of lecture classes by majority of our students.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations